2022
DOI: 10.3390/beverages8020030
|View full text |Cite
|
Sign up to set email alerts
|

From Ground to Glass: Evaluation of Unique Barley Varieties for Craft Malting, Craft Brewing, and Consumer Sensory

Abstract: Differentiating agricultural products has been adopted as a strategy to improve farm profitability and thereby business sustainability. This study aimed to evaluate unique barley varieties for craft malting and brewing markets to enhance profitability for diversified grain growers in southwestern Washington. Advanced barley breeding lines from Washington State University (WSU) were compared to a control variety (CDC-Copeland) through field trials, experimental and commercial malting conditions, and consumer se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Furthermore, in a subsequent study using genotypes also included in this study, Craine et al. (2022) found that malting conditions (experimental or commercial) and field replicate influenced five out of the eight malt quality traits measured, while genotype influenced seven out of eight of the traits. It is critical to consider the malting conditions employed when analyzing and interpreting malt quality for research or selection purposes, as the resulting malt quality is a function of the malting conditions used and likely varies by genotype.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, in a subsequent study using genotypes also included in this study, Craine et al. (2022) found that malting conditions (experimental or commercial) and field replicate influenced five out of the eight malt quality traits measured, while genotype influenced seven out of eight of the traits. It is critical to consider the malting conditions employed when analyzing and interpreting malt quality for research or selection purposes, as the resulting malt quality is a function of the malting conditions used and likely varies by genotype.…”
Section: Discussionmentioning
confidence: 71%
“…A unique market for rye grain is distilled products, such as rye whiskey. As there are not yet publications on breeding rye for local distilling, breeders can look to examples in breeding barley for local malting (e.g., Brouwer et al, 2016;Craine et al, 2021Craine et al, , 2022, and varietal contributions to flavor in distilled products from other crops (Arnold et al, 2019;Kyraleou et al, 2021). Beyond flavor, there is also value in breeding rye cultivars with local or historical connections.…”
Section: Factors Affecting G×ementioning
confidence: 99%
“…"Local microbrewers have caused the circle of potential customers to expand and have contributed to the elevation of the culture of beer knowledge and consumption" [44]. The research conducted by Craine et al [47] revealed that an impressive 83% of respondents indicated their willingness to pay a higher price for beer to assist local farmers. This value proposition offers a chance for consumer spending to provide vital support to producers, who play a crucial role in the craft malt and beer value chain.…”
Section: Local and Authentic Experiencementioning
confidence: 99%